The Importance of Instilling Islamic Aqidah in Elementary School Students in Facing Moral Challenges in the Digital Era: A Literature Review - Mustakim (Indonesian Journal of Education and Science, 2025)
In the digital era, elementary school students face increasing exposure to online environments that pose both opportunities and moral challenges. This study explores the importance of instilling Islamic aqidah (faith-based belief) in elementary students to strengthen their moral resilience in navigating digital spaces. Employing a qualitative library research method with a systematic literature review design, the study analyzed 25 scholarly sources published between 2020 and 2025. Data were collected using thematic coding focused on four areas: conceptual foundations of aqidah, pedagogical strategies, digital-era moral challenges, and innovations in Islamic education. The findings indicate that the internalization of aqidah significantly influences students’ ethical behavior online by fostering digital responsibility, empathy, integrity, and spiritual awareness. However, Islamic elementary schools encounter several challenges in integrating aqidah into digital curricula, such as a lack of integrated pedagogical models, inadequate teacher training, and external pressures that prioritize digital skills over spiritual formation. The study also identified effective strategies for aqidah education in the digital age, including faith-based digital tools, reflective discussions, teacher role modeling, and school-parent collaboration. These findings suggest that a holistic, technology-integrated, and value-oriented approach is essential to moral education in Islamic schools. This study contributes to the development of spiritually grounded and digitally literate educational practices for young Muslim learners.